2019
DOI: 10.1371/journal.pone.0215239
|View full text |Cite
|
Sign up to set email alerts
|

First cytogenetic information for Lonchothrix emiliae and taxonomic implications for the genus taxa Lonchothrix + Mesomys (Rodentia, Echimyidae, Eumysopinae)

Abstract: The taxonomic identification of Lonchothrix emiliae (Rodentia, Echimyidae, Eumysopinae) is problematic because of the overlap of morphological characters with its sister clade represented by species in the genus Mesomys which, like L . emiliae , is distributed throughout the Amazonian biome. Cytogenetic studies reported the karyotype of L . emiliae as 2n = 60/FN = 116, but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(32 citation statements)
references
References 30 publications
7
24
1
Order By: Relevance
“…The specimen of Mesomys stimulax studied herein has 2n = 60 and FN = 110, with 26 pairs of biarmed chromosomes, three small acrocentric pairs, and a medium-size submetacentric X chromosome (Figure 3a; Figure S2). Constitutive Heterochromatin (CH, Figure 3b Mesomys hispidus (Dias de Oliveira et al, 2019;Orlando et al, 2003;Patton et al, 2000) shares the same 2n and FN of the previously reported specimens of M. stimulax (Patton et al, 2000) and probably shares the same chromosomal differences with the karyotype of M. stimulax herein described. In our sample, more CH was present in the centromeric and pericentromeric regions of almost all pairs, with some large blocks observed in pairs 21, 23, and 26 (Figure 3b) while in M. hispidus there are no such large blocks (Dias de Oliveira et al, 2019).…”
Section: Karyotypesupporting
confidence: 62%
See 3 more Smart Citations
“…The specimen of Mesomys stimulax studied herein has 2n = 60 and FN = 110, with 26 pairs of biarmed chromosomes, three small acrocentric pairs, and a medium-size submetacentric X chromosome (Figure 3a; Figure S2). Constitutive Heterochromatin (CH, Figure 3b Mesomys hispidus (Dias de Oliveira et al, 2019;Orlando et al, 2003;Patton et al, 2000) shares the same 2n and FN of the previously reported specimens of M. stimulax (Patton et al, 2000) and probably shares the same chromosomal differences with the karyotype of M. stimulax herein described. In our sample, more CH was present in the centromeric and pericentromeric regions of almost all pairs, with some large blocks observed in pairs 21, 23, and 26 (Figure 3b) while in M. hispidus there are no such large blocks (Dias de Oliveira et al, 2019).…”
Section: Karyotypesupporting
confidence: 62%
“…Constitutive Heterochromatin (CH, Figure 3b Mesomys hispidus (Dias de Oliveira et al, 2019;Orlando et al, 2003;Patton et al, 2000) shares the same 2n and FN of the previously reported specimens of M. stimulax (Patton et al, 2000) and probably shares the same chromosomal differences with the karyotype of M. stimulax herein described. In our sample, more CH was present in the centromeric and pericentromeric regions of almost all pairs, with some large blocks observed in pairs 21, 23, and 26 (Figure 3b) while in M. hispidus there are no such large blocks (Dias de Oliveira et al, 2019). The difference in FN may be due to pericentric inversions or centromeric repositioning (Rocchi et al, 2012), while the variation in amount of CH is likely to reflect the addition/ deletion of repetitive sequences.…”
Section: Karyotypesupporting
confidence: 62%
See 2 more Smart Citations
“…Lonchothrix emiliae lives in lowland mature and secondary (capoeira) rainforests in a limited area of eastern Brazilian Amazonia (Patton 2015b;Fabre et al 2016). Mesomys has a wider geographic range, occupying lowland rainforest throughout the Amazon Basin and the Guianan region, and even extending up to an elevation of 2000 m in the upper montane forests along the eastern slope of the Andes (Patton et al 2000;Voss et al 2001;Orlando et al 2003;Upham et al 2013;Dias de Oliveira et al 2019). Preserved morphology in Paralonchothrix does not allow reliable inference on its habits.…”
Section: Discussionmentioning
confidence: 99%